Simba Kuat: Implementation of an Environmental Cadre Program from School to Village Level in Keluang Village, Tunkal Ilir, South Sumatra - Aprillia, Eka; Hendrawan, Wawan; Abistya, Risang Raditya (CV. Proaksara Global Transeduka, 2024)
Since its inception in 2021 at SMP Negeri 2 Tungkal Ilir, the Synergy Towards a Healthy and Civilized School (Simba Sehati) program has successfully produced environmental cadres through the concept of an environmentally friendly school. Students have become familiar with and skilled in applying Clean and Healthy Living Behavior (PHBS), environmental conservation efforts, and organic farming. The skills acquired include waste bank management, maggot cultivation from organic waste, wastewater treatment, biopore hole creation, hydroponic cultivation of Family Medicinal Plants (TOGA), fish farming in buckets (